Variations in bilingualism and its effects on executive functioning in preschoolers : exploring the relationship between balance in bilingualism and different facets of executive functioning - Ng, Jessica Kai Lun (2019)
The relationship between bilingualism and cognitive control has long been a topic of interest in literature. Bilinguals have been consistently reported to outperform monolinguals on several tasks of executive function, a phenomenon described as the bilingual advantage. However, findings as to which areas of cognition are enhanced remain unclear. In addition, the experience of bilingualism is extremely varied and few studies have studied the bilingual advantage within bilinguals. The relative balance between a bilingual’s two languages, in particular, was speculated to influence the magnitude of the bilingual advantage. Hence, this study aims to look into the relationship between relative balance of the two languages and two aspects of executive functioning: attentional control and cognitive flexibility. The study examined 50 Singaporean English-Mandarin preschoolers who had exposure to both languages before the age of three (29 unbalanced bilinguals, 21 balanced bilinguals). Findings revealed little support for a bilingual advantage - the two groups did not differ in interference effects assessed in the Flanker Attention and Inhibition Task, or for switching and mixing costs assessed in the Dimensional Change Card Sort Task. This suggests that there is a need to re-evaluate the limits of the bilingual advantage and for closer inspection on what aspect of a bilingual can result in an advantage, under what conditions and why.